PENGARUH KUALITAS KERJA DAN DISPLIN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI PT. DAMAI ABADI MEDAN - Sri Prianka (JOURNAL ECONOMICS AND STRATEGY, 2023)
Employee work effectiveness is one of the factors that play an important role in organizational activities that need to be fostered and developed so that organizational goals can be achieved effectively. This study aims to determine the effect of work quality and work discipline on work effectiveness. This study used a questionnaire as a data collection technique with a total sample of 80 people. The data analysis technique used is multiple linear regression. The results showed that the quality of work and work discipline partially and simultaneously had a significant effect on the work discipline of PT Damai Abadi Medan employees, this could be seen from the sig value of less than 0.05. The RSquare value is 0.897 or R2 x 100% which is 89.70%, meaning that the independent variables of the research make a major contribution in explaining the effectiveness of employee work by 89.70% while the remaining 10.30% is influenced by other factors outside the research.